The Virtual Dakwah In Pandemic Covid-19 Era - Kurniati Abidin; Rasyidah Zainuddin (State Islamic Institute of Bone, Indonesia, 2020)
This research intends to reveal the process of dakwah through the virtual world (internet) during the Pandemic Covid-19 period. It is not really felt the difference between the virtual propaganda model during the pandemic with the previous period, but there are several variants that can be observed as these differences. This research is qualitative descriptive with a focus on the process of virtual preaching. Data is collected from prosecutors (da'i) through semi-structured interviews accompanied by observations, and literature studies. Existing data were analyzed using Cresswell's approach such as data categorization, reduction, and conclusion drawing. The results showed that virtual propaganda took place in the form of the use of online video, the use of online text messages and images (online massage), the use of voice messages (MP3), and the use of online streaming. The dakwah model still uses platforms that are already available in the virtual world (the internet), both existing ones such as Webex, Youtu.be and the latest versions such as Zoom, Google Meet, and so on. The conclusion of this study is that the virtual dakwah model follows the use of the existing platform and the preachers adapt to the characteristics of the platform. Even so, the virtual world always has both positive and negative sides.